Prevalence of Priapism and Its Awareness amongst Male Homozygous Sickle Cell Patients in Lagos, Nigeria - Adewumi Adediran; Kikelomo Wright; Akinsegun Akinbami; Adedoyin Dosunmu; Olajumoke Oshinaike; Bodunrin Osikomaiya; Sarah Ajibola; Kamal Ismail; Ebele Uche; Olaitan Ojelabi (Advances in Urology, 2013)
Background. Priapism is a pathological condition of penile erection that persists beyond, or is unrelated to, sexual stimulation. Impotence and infertility are major problems in male sickle cell disease patients, and priapism has been implicated as a cause of impotence and infertility. The aim of this study is to determine priapism prevalence and assess the knowledge of male homozygous male patients about it in Lagos, Nigeria. Methods. A cross-sectional study was conducted amongst male homozygous sickle cell disease patients of Lagos State University Teaching Hospital. Pretested questionnaires were distributed to determine the prevalence and assess their knowledge on priapism. Data were analyzed using SPSS version 16.0. Results. A total of 114 consenting subjects filled the questionnaires, 85 of 114 (74.6%) had not heard about priapism before this study. A total of 77 of 114 (67.5%) did not know that they are at risk of priapism. Whilst 84 of 114 (73.7%) were not aware that priapism is a complication of SCD. The majority, 94 of 114 (82.5%), were not aware that priapism could cause impotence. Conclusion. There is a need to create more awareness about this complication amongst sickle cell disease patients in order to stem the incidence of impotence and infertility amongst them.